Managing learning in virtual settings the role of context - Figueiredo, Antonio Dias 1946-; Afonso, Ana Paula 1973- (Gale virtual reference library, 2006)
"This book emphasizes the role of context in the development and management of virtual learning environments"--Provided by publisher.